CHALLENGING SPATIAL MARGINALIZATION THROUGH SOCIAL MEDIA COMMUNICATION? A CASE STUDY OF THE TWITTER DISCOURSE ON HOUSING IN BERLIN - Stoltenberg, Daniela (AoIR Selected Papers of Internet Research, 2020)
Urban public life has historically and famously been structured by social stratification and a segregation of social milieus. Such spatialized social inequality along the lines of, most importantly, class, age, and ethnicity engenders unequal access to civic participation and supportive social networks. Meanwhile, the Internet and Web 2.0 technologies in particular have often been hailed for their potential of bringing underrepresented voices into the public discourse and even creating so-called “networked counterpublics”, challenging social power structures. This contribution seeks to address the question of whether social media communication about urban issues challenges or reproduces patterns of spatial inequality in its attention distribution. Empirically, it investigates the distribution of place-naming within the Berlin-based Twitter discourse on housing. It finds that - while issue attention in the urban Twitter discourse is clearly spatially unequal, with a striking imbalance between center and periphery - neither sociodemographic composition nor issue characteristics perform well in explaining these patterns. Instead it proposes focusing more on local civic and activist infrastructure in future research.